Multicultural Education in Islam to Strengthen the Religious Character of Gen Z in Indonesia - Siti Nurhalimatussadiyah; Lismawati; Nurul Aisyah (Universitas Wahid Hasyim Semarang, 2025)
Dalam artikel ini, peneliti akan mendalami dampak mendalam pendidikan multikulturalisme terhadap generasi muda generasi Z, khususnya dari sudut pandang Islam. Pendekatan unik ini tidak hanya menggali aspek-aspek positif dalam memupuk pemahaman tentang keragaman budaya dan mendorong toleransi, namun juga memasukkan nilai-nilai fundamental Islam seperti kasih sayang, keadilan, dan kerja sama untuk membentuk karakter generasi Z. Tujuan utama dalam kajian adalah Multicultural education is an idea designed with the intention to bring about equality in educational opportunities for all students and community members, regardless of differences in racial identity, ethnicity, social level, and cultural diversity. The main objective in the study is to equip Generation Z with inclusivity, respect for differences, and the ability to make positive contributions to a society that thrives on multiculturalism. The methodology used is qualitative, through the application of the Systematic Literature Review (SLR) technique to explore the issues discussed. A total of 8 articles were used as the main material in this research study which were indexed with ISSN (International Standard Serial Number). Data collection was obtained from google search/google scholar and in the time span between 2015 and 2024. Based on the research, it shows that multiculturalism education based on Islamic perspectives has a positive impact on Generation Z character building. Keywords: Generation z characters; Islamic multiculturalism; Multiculturalism Education.